2022
DOI: 10.1111/clr.13959
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative complications and early implant failure after transcrestal sinus floor elevation with residual bone height ≤5 mm: A retrospective multicenter study

Abstract: Objective Clinical indications for maxillary sinus floor elevation with transcrestal techniques have increased in recent years even in sites with minimal residual bone height (RBH). Nevertheless, limited information is currently available on incidence of intraoperative complications and early implant failure in these cases. Material and Methods This retrospective multicenter study was performed on anonymized clinical and radiographic records of patients who underwent transcrestal sinus floor elevation in seven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
(62 reference statements)
0
20
1
2
Order By: Relevance
“…A previous systematic review including 7358 implants indicated that membrane perforation in the sinus augmented procedure could increase the risk of implant failure [ 39 ]. Additionally, a recent multicenter study of 430 implants, also confirmed that the sinus membrane perforation [OR 4.21; 95% CI (1.10–16.05); P = 0.035] had a statistically significant effect on early implant failure [ 40 ]. This could be explained as follows: the membrane perforation may result in local inflammation, influence the remolding of grafting material, reduce bone formation and ultimate implant loss.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A previous systematic review including 7358 implants indicated that membrane perforation in the sinus augmented procedure could increase the risk of implant failure [ 39 ]. Additionally, a recent multicenter study of 430 implants, also confirmed that the sinus membrane perforation [OR 4.21; 95% CI (1.10–16.05); P = 0.035] had a statistically significant effect on early implant failure [ 40 ]. This could be explained as follows: the membrane perforation may result in local inflammation, influence the remolding of grafting material, reduce bone formation and ultimate implant loss.…”
Section: Discussionmentioning
confidence: 91%
“…The intro-sinus bone formation has been verified to be more in narrow sinuses than in wider sinuses [52,53]. Meanwhile, based on the logistic regression analysis, a significant correlation was found between larger sinus cavities [OR 8.50; 95 CI (1.02-70.42); P = 0.047] and early implant failure [40].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It was supposed that Schneiderian membrane perforation increased the risk of postoperative sinusitis, and implant failure. 49,50 Non-repair of the Schneiderian membrane perforation had higher intraoperative and postoperative complications. 5 It has been found that the new bone formation was adversely affected by the membrane perforation in a rabbit model.…”
Section: Discussionmentioning
confidence: 99%